Narrativas de professores de inglês de escolas públicas e o seu caráter revelador - Geraldo, Carla Cristiane (2013)
The aim of this study was to analyze narratives of English language teachers from public schools in São Carlos and Araraquara from the 1950s to 2012, so as to understand the changes that have occurred in the teaching of that language in public schools that led to the crisis it faces nowadays. This crisis is related to school violence, to widespread disaffection, and to dissatisfaction and low self-esteem of students, teachers and school leaders. The methodology used for data collection was the oral history of the teachers career paths. The data was analyzed qualitatively, allowing a panoramic view of the changes that have occurred in the teaching of English over the last 60 years. The analysis of the narratives revealed that the crisis results from a long historical process of changes, where two huge forces have affected negatively the pedagogical and social/personal dimension of the English language classroom. In this conflict the largest unbalancing factor falls upon the institutional changes, and the smallest falls upon the unavoidable force of the social and family values.